2019
DOI: 10.1073/pnas.1821475116
|View full text |Cite
|
Sign up to set email alerts
|

Replication fork stalling elicits chromatin compaction for the stability of stalling replication forks

Abstract: DNA replication forks in eukaryotic cells stall at a variety of replication barriers. Stalling forks require strict cellular regulations to prevent fork collapse. However, the mechanism underlying these cellular regulations is poorly understood. In this study, a cellular mechanism was uncovered that regulates chromatin structures to stabilize stalling forks. When replication forks stall, H2BK33, a newly identified acetylation site, is deacetylated and H3K9 trimethylated in the nucleosomes surrounding stalling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 50 publications
(66 reference statements)
2
12
0
Order By: Relevance
“…Notably, we observed that HU treatment induces global chromatin compaction that partially depends on Mrc1, leading to the blockage of the access of chromatin remodeling factors and resection machinery ( Figures 7A,B ). This is consistent with the observation that replication stress also triggers chromatin compaction in fission yeast (Feng et al, 2019 ). It was reported that replication stress induces the deacetylation of histone H2B-K33ac by Clr6 and the enrichment of H3K9 tri-methylation at stalled forks, which contributes to the formation of a compacted chromatin environment (Feng et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Notably, we observed that HU treatment induces global chromatin compaction that partially depends on Mrc1, leading to the blockage of the access of chromatin remodeling factors and resection machinery ( Figures 7A,B ). This is consistent with the observation that replication stress also triggers chromatin compaction in fission yeast (Feng et al, 2019 ). It was reported that replication stress induces the deacetylation of histone H2B-K33ac by Clr6 and the enrichment of H3K9 tri-methylation at stalled forks, which contributes to the formation of a compacted chromatin environment (Feng et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the observation that replication stress also triggers chromatin compaction in fission yeast (Feng et al, 2019 ). It was reported that replication stress induces the deacetylation of histone H2B-K33ac by Clr6 and the enrichment of H3K9 tri-methylation at stalled forks, which contributes to the formation of a compacted chromatin environment (Feng et al, 2019 ). Constitutive mimic acetylation of H2B-K33ac leads to uncoupling of replicative helicase and DNA polymerases and replication fork instability (Feng et al, 2019 ).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Meanwhile macroH2A is associated with compact chromatin, and it is a possibility that reduced macroH2A at the fork leads to greater accessibility. A recent report studying S. pombe cells found that chromatin compaction at the stalled fork protects, whereas chromatin relaxation is associated with greater fork instability 70 . Our model suggests that LSH acts globally on macroH2A deposition, but that an unfavorable pre-lesion chromatin environment at the replication fork promotes fork degradation.…”
Section: Discussionmentioning
confidence: 99%